704. Evaluation of Risk Factors and Outcomes of Early Left Ventricular Assist Device Infections. (31st December 2020) - Shealy, Stephanie; Milgrom, Alexander; burns, Stephen; Ferraro, Hunter; Collins, Amanda; Cox, Jenna; Derrick, Caroline; Mardis, Andrew; Grubbs, James; Weissman, Sharon; Justo, Julie Ann; Bookstaver, P B
Abstract: Background: Infection is a major complication of placement of left ventricular assist devices (LVADs) for patients with end stage heart failure. This study aimed to identify risk factors and evaluate outcomes of early LVAD specific and related infections in a community teaching hospital. Methods: This was a single-center, retrospective cohort study that included adult patients with placement of LVAD from October 2012 – December 2019. LVAD specific infection was defined as a pump, cannula, pocket, or percutaneous driveline infection and LVAD related infection was defined as infective endocarditis, mediastinitis, or bloodstream infection. The primary outcome was early LVAD specific or related infection within 90 days of implantation. Secondary outcomes included time to infection, risk factors of and time to recurrent infection, and time to death. Multivariate logistic regression was used to ascertain risk factors for early infection. Cox regression was used to ascertain association with time to outcome variables. Results: Of 160 patients who had LVADs placed during the study period, 26 experienced early LVAD infection. The majority of infections were caused by Staphylococcus spp. (32.1%). Risk factors for early infection are summarized in Table 1. Risk factors identified included placement of HeartMate III device when compared to HeartMate II and BMI > 40kg/m 2 . Increased hazard rate of infection was demonstrated for patients with HeartWare and HeartMate III devices compared to HeartMate II (HR 2.344; 95% CI 1.22, 4.496; p-value 0.01; and HR 2.858; 95% CI 1.231, 6.635; p-value 0.015, respectively), those with BMI >40 (HR 2.437; 95% CI 1.131, 5.252; p-value 0.023), and those with history of diabetes (HR 1.736; 95% CI 1.012, 2.987; p-value 0.045). No risk factors were identified in the multivariate regression model for recurrent infection. Time to death was increased among patients with A1C > 6.4 at baseline (HR 1.028; 95% CI 1.002, 1.054; p-value: 0.032) and among patients who experienced early LVAD infection (HR 3.824; 95% CI 1.928, 7.584; p-value < 0.001). Conclusion: HeartMate III device and BMI > 40kg/m 2 were identified as risk factors for early LVAD infection. Time to mortality was decreased among patients that experienced an early LVAD infection. Disclosures: Julie Ann Justo, PharmD, MS, BCPS-AQ ID, bioMerieux (Speaker's Bureau)TRC Healthcare (Speaker's Bureau)